2015
DOI: 10.1007/s00423-015-1316-9
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of adhesiolysis on chronic abdominal pain: a systematic review

Abstract: The identified studies showed promising but preliminary results of laparoscopic adhesiolysis as a treatment of chronic abdominal pain. The evidence for laparoscopic adhesiolysis is not sufficient to make definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
0
6
0
3
Order By: Relevance
“…When grouping our patients according to prior or non-prior abdominal surgery, we measured a higher pain level in patients without pre-existent surgery (Fig. 5 A), which may be due to the fact, that in pre-operated patients with a likelihood for adhesions in 40–63% of gynecological or obstetric patients, [ 37 ] pain relief by adhesiolysis may have been beneficial per se [ 38 , 39 ]. Nonetheless, the use of WHCD leads to a significant reduction of pain in the patient group facing higher pain levels.…”
Section: Discussionmentioning
confidence: 99%
“…When grouping our patients according to prior or non-prior abdominal surgery, we measured a higher pain level in patients without pre-existent surgery (Fig. 5 A), which may be due to the fact, that in pre-operated patients with a likelihood for adhesions in 40–63% of gynecological or obstetric patients, [ 37 ] pain relief by adhesiolysis may have been beneficial per se [ 38 , 39 ]. Nonetheless, the use of WHCD leads to a significant reduction of pain in the patient group facing higher pain levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent literature review does not convincingly support that adhesiolysis is enough to improve abdominal and/or pelvic pain. 30 Based on many controversial and inconclusive data, we can only deduce that there is a complexity not yet disclosed on the role of peritoneal adhesion in the genesis of CPP.…”
Section: Cpp Originating In Peritoneal Adhesionsmentioning
confidence: 99%
“…However, the incidence of adhesions varies widely in the literature (45%–100%), and causal relationships to abdominal pain have been difficult to prove. No non‐invasive tests are available to diagnose abdominal adhesions, but most are identified during exploratory surgery 27,28 . Laparoscopic adhesiolysis has been proposed as a treatment for PAP 28 .…”
Section: Pap Linked To a Digestive Disordermentioning
confidence: 99%
“…Laparoscopic adhesiolysis has been proposed as a treatment for PAP 28 . A systemic review of 25 studies found a positive outcome of adhesiolysis on pain relief, but because the studies lacked controls, these results are hardly discussed 27 . However, the only randomised study comparing adhesiolysis to a sham procedure in patients with chronic abdominal pain demonstrated no beneficial effect of adhesiolysis after 1‐year follow‐up, 71 and after 12 years of follow‐up, patients with adhesiolysis had more pain, more surgery and more consultations 29 .…”
Section: Pap Linked To a Digestive Disordermentioning
confidence: 99%
See 1 more Smart Citation